MOTIVASI BELAJAR MAHASISWA ANGKATAN 2019 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERISTAS RIAU PADA MATA KULIAH BUNPOU 5 - Novela Otri; Nana Rahayu; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is about the student learning motivation of class 2019 Japanese Language Education Study Program FKIP University of Riau in the study of Bunpou 5. The purpose of this research is to explains how the level of student learning motivation of class 2019 Japanese Language Education Study Program FKIP University of Riau in the study of Bunpou 5. The research type with quantitative approach. The population was student of class 2019 of 33 student. The research instrument is questionnaires. The data analysis technique used is validity and reability test. The result of the research shows that the student learning motivation of class class in the high category with percentace of 54,5%.Key Words: Learning Motivation, Bunpou.